Coordination between the Ministry of Religious Affairs and the Ministry of Education, Culture, Research, and Technology in the Management of Madrasah EMIS to Ensure Accuracy of National Education Planning - Uripah Uripah; Indra Kertati; Charis Christiani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines coordination between the Ministry of Religious Affairs and the Ministry of Education Culture Research and Technology in managing the Madrasah Education Management Information System EMIS. The main issue is data asynchrony that affects the accuracy of national education planning including budget allocation and the distribution of educational social assistance. This study uses Interorganizational Coordination Theory by B Guy Peters and Collaborative Governance by Ansell and Gash. A qualitative approach was used to analyze the data integration process and bureaucratic obstacles in inter institutional relations. The findings show that coordination between the two ministries influences the accuracy of national education planning. However the coordination is still dominated by a formal administrative approach and has not yet achieved substantive collaboration. The main obstacles include sectoral ego low interoperability of information systems and weak data sharing mechanisms. These conditions lead to data redundancy and information gaps that reduce the quality of policy making. Strengthening coordination through facilitative leadership digital integration across ministries and system automation based on interoperability is needed to improve the accuracy of national education planning.